Seminar on the new ICE arbitration procedure Thursday 12 May 1983 at the Institute of Civil Engineers, 1-7 Great George Street, London SW1. (Thomas Telford, 1983)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held in 1983.